2019
DOI: 10.3390/land8120186
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Preferential Water Flow during Natural Vegetation Restoration on Abandoned Farmland in the Loess Plateau of China

Abstract: The restoration of vegetation in abandoned farmlands is an effective approach to control soil erosion on the Chinese Loess Plateau. However, few studies have investigated the effect of natural restoration age on the infiltration patterns and preferential flow in soil layers. This study examined the effect of the temporal variations in the degree of preferential flow and their contribution on the total infiltration in abandoned farmlands restored with different vegetation communities. In total, four sites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This study showed that ET increased with the increase of soil water content in the irrigated area, which indicated that irrigation had a direct impact on AET in arid and semi-arid areas. This result was consistent with other studies [22].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study showed that ET increased with the increase of soil water content in the irrigated area, which indicated that irrigation had a direct impact on AET in arid and semi-arid areas. This result was consistent with other studies [22].…”
Section: Discussionsupporting
confidence: 94%
“…Unlike other parametric tests, the Mann-Kendall test does not require samples to follow a certain distribution pattern and is disturbed by abnormal values; therefore, this method is more suitable for testing sequential variables. A Mann-Kendall test had been successfully used to test hydrological and meteorological time-series data for determining whether the data showed an upward or downward trend [22,23].…”
Section: Methodology 231 Theil-sen Median Trend Analysis and Mann-ken...mentioning
confidence: 99%
“…Although soil profile staining images can visualise the basic morphological characteristics of preferential flow, specific characteristic parameters and statistical models are needed to quantify preferential flow when the overall development of preferential flow is to be assessed. The preferential flow morphological parameters obtained in this study showed that the DC of the karst region is lower than that of the northwest loess region [30], semi-arid grassland in northern China [31], and Three Gorges purple soil region [32]. This difference may be due to the fact that the soil in this study area is limestone red soil with a large water holding capacity but minimal available water and low saturated water conductivity [33,34]-conditions not conducive to the infiltration of water into deep layers.…”
Section: Preferential Flow Characteristics In the Typical Forests Of ...mentioning
confidence: 57%
“…Cropland converted to grassland after abandonment increases soil moisture (An et al, 2017). At the same time, the migration of rural residents and increased urbanization have rapidly increased the amount of abandoned land in the past few years (Wang et al, 2011(Wang et al, , 2019. Due to the abovementioned reasons, an adjustment to the vegetation restoration planting structure transformed the spatial pattern of land use types, significantly increasing the grassland area.…”
Section: Analysis Of Lulccmentioning
confidence: 99%